Spin-Crossover Materials : Properties and Applications. - Halcrow, Malcolm A. (Wiley, 2013)
Beginning with an introductory chapter describing the spin-crossover phenomenon and a historical overview of the field since it was first observed in the 1930s, this book looks at recent advances in the chemistry of "traditional" spin-crossover complexes and materials containing iron(II), iron(III) or cobalt(II). Other topics include various types of spin-state transition, multi-functional and nanoscale spin-crossover materials, and new experimental and theoretical discoveries about the physical mechanism of spin-crossover at the molecular level and in bulk materials.